How the ICT development level and usage influence student achievement in reading, mathematics, and science - Skryabin, Maxim; Zhang, JingJing; Liu, Luman; Zhang, Danhui (Computers and education, 2015)
The main purpose of this study is to investigate how national ICT development level and individual ICT usage will influence achievements in reading, mathematics, and science for 4th and 8th grade school students. Large-scale international databases, including TIMSS 2011, PIRLS 2011, and PISA 2012, were employed in the current study. Hierarchical linear models (HLM) were applied to examine both country- and individual-level variables. According to the findings of this study, the national ICT development level is a significant positive predictor for individual academic performance in all three subjects for both 4th grade and 8th grade students, while the national economic development level was controlled for. Such finding indicates a similar trend of the ICT influences for both groups, although there exists a difference in terms of the extent of the relationships. In addition, individual-level ICT use is a significant predictor, even if students' gender and socioeconomic status are controlled for; however, its influence is mixed across different student groups and subjects depending on the ICT usage type. •Three Large-scale international assessments including PISA, TIMSS, & PIRLS were used.•With national GDP was controlled for, the positive effects of national ICT level on individual achievements were discovered.•Similar trend of national ICT influences on individual achievement was observed for both 4th and 8th grade.•Personal ICT usage showed mixed influences on student achievement, depending on different usage type.